PELATIHAN MEMBUAT MEDIA PEMBELAJARAN BERBASIS CANVA DI MTs DALWA PASURUAN - Asep Rahmatullah; Faisol Hakim (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
Islamic Religious Education (PAI) teachers in pesantren-based madrasahs face a dual challenge: mastering religious content while delivering it digitally to Generation Z students. This community service program aimed to enhance the competence of PAI teachers at MTs Dalwa Pasuruan in designing innovative learning media using the Canva application. An initial survey revealed that only 24% of the 25 participating teachers had previously used digital design applications for instructional purposes. The program was conducted on December 16, 2025, at the MTs Dalwa Computer Laboratory, employing a participatory training method with a hands-on approach encompassing four phases: socialization, introduction to Canva features, guided independent practice, and evaluation of outputs. Assessment results demonstrated significant improvement across all evaluated dimensions: the overall mean score increased from 43.4 on the pre-test to 81.1 on the post-test, with the greatest gain of 48.2 points recorded in Canva proficiency. A total of 76% of participants successfully completed an independent PAI learning media product within the training period, and the overall participant satisfaction rate reached 91.2%. These findings confirm that hands-on participatory training is effective in developing digital competencies among PAI teachers in madrasah settings with previously limited technology access. Replication of this program at other madrasahs in Pasuruan Regency is recommended, with the addition of structured post-training mentoring sessions.